As associações nacionais e internacionais de Doença de Chagas: uma rede social para a efetividade do direito à saúde - 1987/2012 - Silva, Maria Barbosa da (2014)
This thesis studies the experience of the process of foundation of a network of national and international Chagas disease associations that focuses on the effectiveness of the human right to health care. The general objective is to analyze the foundation and the development process of the national and international Chagas disease associations during the years of 1987 to 2012, culminated with the construction of a democratic full time network of assistance to the carrier of the disease that also aims at better life and health conditions to them. The guiding question of this thesis is: do the national and international Chagas disease associations, on their own and on networks, constitute a democratic strategy that enables the accomplishment of the right of access and the effectiveness of the assistance to the carriers of the disease and of better life and health conditions? The hypothesis is: the Chagas disease associations, as national and international networks - FINDECHAGAS -, are constituted by a democratic strategy as they enable an increasing awareness of the Chagas disease as a public health issue and gives the opportunity to its partners to participate actively and collectively aiming the achievement and effectiveness of the full time assistance to the disease and for better life and health conditions to its carriers. The main conceptual references handle associativism, democracy, citizenship, participation and social network approached by notorious authors of the Biological and Social Sciences field. From the methodological point of view, nature of the research is qualitative and includes documental, bibliographic and field researches. Ten testimonies of participants of the research were collected and they showed, along with the observer opinion of this researcher, that the experience of the process of foundation of a network of national and international Chagas disease associations is constituted by a democratic strategy, and it confirms the hypothesis first proposed. This outcome, despite the foundation/implement stage of the FINDECHAGAS, evidences, however, the need of strengthening the bounds, relations and articulation among the network in face of the challenges such as the increase and improvement of the quality of assistance in national and global levels to the carriers of the Chagas disease, considering, in this sense, the deepening democratic historic contexts of countries, in the present and in the future